Structure and immunogenicity of pre-fusion-stabilized human metapneumovirus F glycoprotein - Michael B. Battles (Nature Portfolio, 2017)
An efficient vaccine for human metapneumovirus (hMPV) will likely rely on neutralizing antibodies against the fusion protein (F). Here, the authors determine the crystal structure of pre-fusion-stabilized hMPV F and identify a dense glycan shield that affects generation of neutralizing antibodies.